INFLUENCE OF TEMPERATURE AND HUMIDITY CONDITIONS ON WATER ABSORPTION OF LIGHT CONCRETES ON GROUND AGGREGATES - Bakhodir Rizayev, Islombek Akhmedov, Shavkat Yusupov , Isroiljon Umarov, Aleksandr Kazadayev, Farrukh Dadakhanov (Journals Park Publishing, 2022)
This article is devoted to the theoretical and experimental study of the change in the temperature and humidity regime in light concretes on porous aggregates for the water absorption of concrete. The obtained data indicate that with an increase in bulk mass and with the use of ordinary sand as a fine aggregate, the water absorption of concretes on the investigated porous aggregates decreases.
Keywords: temperature-humidity mode, microcracks, destructive process, concrete durability, alternating moistening and drying, softening factor, concrete water absorption.